(untitled) (Perner’s Contacts, 2023)
This paper focuses on cycling transport in the capital city of the Czech Republic – Prague. Main goal of the paper is to find out whether available measures for cycling transport support are taken there. The authors focus on the infrastructure dedicated for cyclists in Prague and they primarily focus on the safety of the users. Potentially dangerous and/or not comfortable examples are included as well.